2012
DOI: 10.1002/ajmg.a.35710
|View full text |Cite
|
Sign up to set email alerts
|

Growth charts of Turkish children with Down syndrome

Abstract: We present growth curves of 1,726 Turkish children with Down syndrome (DS) between 0 and 18 years of age and investigate the factors that affect growth including congenital heart disease (CHD) and hypothyroidism. Longitudinal measurements of height, weight, and head circumference (HC) were assessed and accompanying major malformations were recorded. Growth curves were monitored using Cole's LMS method. The mean birth length was reduced by À0.5 standard deviation (SD) for Turkish standards in both boys and girl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
3
22
0
Order By: Relevance
“…17 Several research studies show that anomalies associated with DS, especially CHD usually affect physical growth patterns. 11,13,14 The number of DS children with CHD in our study is 47%, which is relatively similar to the existing literature of 40 to 50%, 7 53% of the samples in the United States 2015 study, 12 and 50% in the Chinese study. 20 Our growth patterns demonstrate both weight and length/height differences between the DS children with CHD and without CHD in both genders, and the differences are more noticeable in girls.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…17 Several research studies show that anomalies associated with DS, especially CHD usually affect physical growth patterns. 11,13,14 The number of DS children with CHD in our study is 47%, which is relatively similar to the existing literature of 40 to 50%, 7 53% of the samples in the United States 2015 study, 12 and 50% in the Chinese study. 20 Our growth patterns demonstrate both weight and length/height differences between the DS children with CHD and without CHD in both genders, and the differences are more noticeable in girls.…”
Section: Discussionsupporting
confidence: 87%
“…Turkish children with DS who have severe CHD have a significantly lighter weight than those without CHD from the age of 3 months to 4 years old. 13 Dutch DS children with severe CHD are significantly shorter and have a smaller head circumference than those without CHD. 14 Similarly, United States DS children with severe CHD, who are younger than 8 years old, are approximately 1.5 to 2 cm shorter in length/height and 0.5 to 2 kg lower in weight than the general children.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…10 . However, a study of the Turkish population with SD 23 showed no statistically significant differences between the groups with or without severe heart disease and or hypothyroidism.…”
Section: Discussionmentioning
confidence: 91%